Hubungan Penambahan Berat Badan Ibu Selama Hamil dan Kepatuhan Kunjungan Antenatal Care (ANC) dengan Berat Lahir Bayi - Samiya Zuhrotud Diana (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
One of the leading factors contributing to neonatal mortality is low birth weight (LBW), which is often associated with maternal conditions such as Chronic Energy Deficiency (CED). Cases of CED remain relatively common in the operational area of Puskesmas Turi. In 2022, East Java reported an LBW prevalence of 3.96%, which is 0.66% higher than the national average. The coverage of antenatal care (ANC) visits shows a declining trend: 100.8% for the first visit (K1), 94% for the fourth visit (K4), and only 83.1% for the sixth visit (K6), indicating irregular adherence to ANC schedules among pregnant women.This study aims to evaluate the relationship between infant birth weight and maternal weight gain during pregnancy, as well as the level of ANC compliance in the Puskesmas Turi area. The study design employed a cross-sectional approach with a multistage random sampling technique involving 84 mothers. Data were collected through direct interviews and documentation from the maternal and child health (KIA) book. Data analysis was conducted using the chi-square test and Fisher exact test. The results revealed a significant association between maternal weight gain and infant birth weight (p = 0.000), as well as between ANC compliance and infant birth weight (p = 0.002). The role of health cadres is crucial in improving ANC adherence and the nutritional status of pregnant women.